2010
DOI: 10.3934/dcds.2010.28.559
|View full text |Cite
|
Sign up to set email alerts
|

Partial regularity of Brenier solutions of the Monge-Ampère equation

Abstract: Given Ω, Λ ⊂ R n two bounded open sets, and f and g two probability densities concentrated on Ω and Λ respectively, we investigate the regularity of the optimal map ∇ϕ (the optimality referring to the Euclidean quadratic cost) sending f onto g. We show that if f and g are both bounded away from zero and infinity, we can find two open sets Ω ′ ⊂ Ω and Λ ′ ⊂ Λ such that f and g are concentrated on Ω ′ and Λ ′ respectively, and ∇ϕ : Ω ′ → Λ ′ is a (bi-Hölder) homeomorphism. This generalizes the 2-dimensional part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 11 publications
0
55
0
3
Order By: Relevance
“…As shown in [52] (see also [50] for a more precise description of the singular set in two dimensions), in this case one can prove that the optimal trasport map is smooth outside a closed set of measure zero. More precisely, the following holds: Theorem 3.4.…”
Section: Theorem 32 (Alexandrov)mentioning
confidence: 96%
See 1 more Smart Citation
“…As shown in [52] (see also [50] for a more precise description of the singular set in two dimensions), in this case one can prove that the optimal trasport map is smooth outside a closed set of measure zero. More precisely, the following holds: Theorem 3.4.…”
Section: Theorem 32 (Alexandrov)mentioning
confidence: 96%
“…In the quadatic cost case, in [50,52] it was shown that on a big set there is still a good control on the Monge-Ampère measure of the potential u allowing to apply the local theory of classical Monge-Ampère equation, see the sketch of the proof of Theorem 3.4. However, the failure of the MTW condition does not allow us to use any local regularity estimate for the PDE, therefore a completely new strategy with respect to [50,52] has to be used.…”
Section: Mtw Vs Cut-locusmentioning
confidence: 99%
“…As shown in [51] (see also [49] for a more precise description of the singular set in two dimensions), in this case one can prove that the optimal transport map is smooth outside a closed set of measure zero. More precisely, the following holds.…”
Section: G De Philippis and A Figallimentioning
confidence: 97%
“…In addition, since u is close to a parabola, so is v. Hence, by [18] and Caffarelli's regularity theory, v is smooth, and we can use this information to deduce that u is even closer to a second parabola (given by the second order Taylor expansion of v at the origin) inside a small neighborhood around of origin. By rescaling back this neighborhood at scale 1 and iterating this construction, we obtain that u is C 1,β at the origin for some β ∈ (0, 1).…”
Section: β Regularity and Strict C-convexitymentioning
confidence: 99%
“…In [16,18] the authors proved the following result: Theorem 1.2. Let f and g be smooth probability densities, respectively bounded away from zero and infinity on two bounded open sets X and Y , and let T : X → Y denote the unique optimal transport map from f to g for the quadratic cost |x − y| 2 /2.…”
Section: Introductionmentioning
confidence: 99%